(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2012)
Regarding the impact of equity onthe return and volatility of underlying stock market, the study revealed thatthere is a significant increase in return after the introduction of indexfutures in S&P CNX Nifty. However, this effect disappeared after theintroduction of index options. It means price reversal was found only for awhile after the introduction of derivatives and the market came again inequilibrium after getting depth in equity market. In case of individual stocks,majority of the stocks showed no significant difference in the return after theintroduction of stock equity.